From Loopholes to Deinstitutionalization: The Platform Economy and the Undermining of Labor and Social Security Institutions - Beckmann, Fabian; Hoose, Fabian (PARTECIPAZIONE E CONFLITTO, 2023)
Previous research on platform work has concentrated on questions of organization, technology and regulation, while the focus has been much less on institutions and mechanisms by which platform work challenges existing labor market and welfare state institutions. This article deals with platform-driven deinstitutionalization using the example of social security in the conservative German welfare state. We argue that the main feature of platform work is the weakening of labor- and welfare-related institutions. We show how platforms undermine the German social security scheme in a functional perspective by using solo self-employment or minijobs, resulting in varieties of externalization of social protection. Furthermore, the social security institutions are normatively undermined by the strategic use of two main narratives: while the sharing narrative negates power asymmetries and highlights peer-to-peer relationships at eye level, the entrepreneurship narrative promotes ideas of autonomy and self-realization. Both strategies aim at redefining social security institutions and undermining collective protection. We discuss the disruptive effects of platform work and the inability of the social security institutions in Germany to adjust to the digital age and ensure sufficient social protection for workers in non-standard forms of employment. The analysis also implies that future regulatory policies have to take power struggles over cultural framings into account.